Development and clinical validation of a dual ddPCR assay for detecting carbapenem-resistant Acinetobacter baumannii in bloodstream infections - Kou, Xiaoxia; Zhu, Detu; Zhang, Yandong; Huang, Liyan; Liang, Jiawei; Wu, Ziman; Liu, Ze; Guan, Chushi; Yu, Lin (Frontiers in Microbiology, 2024)
Objective Acinetobacter baumannii (A. baumannii, AB) represents a major species of Gram-negative bacteria involved in bloodstream infections (BSIs) and shows a high capability of developing antibiotic resistance. Especially, carbapenem-resistant Acinetobacter baumannii (CRAB) becomes more and more prevalent in BSIs. Hence, a rapid and sensitive CRAB detection method is of urgent need to reduce the morbidity and mortality due to CRAB-associated BSIs. Method A dual droplet digital PCR (ddPCR) reaction system was designed for detecting the antibiotic resistance gene OXA-23 and AB-specific gene gltA. Then, the specificity of the primers and probes, limit of detection (LOD), linear range and accuracy of the assay were evaluated. Furthermore, the established assay approach was validated on 37 clinical isolates and compared with blood culture and drug sensitivity tests. Results The dual ddPCR method established in this study demonstrated strong primer and probe specificity, distinguishing CRAB among 21 common clinical pathogens. The method showed excellent precision (3×10-4ng/μL, CV<25%) and linearity (OXA-23: y=1.4558x+4.0981, R²=0.9976; gltA: y=1.2716x+3.6092, R²=0.9949). While the dual qPCR LOD is 3×10-3ng/μL, the dual ddPCR's LOD stands at 3×10-4ng/μL, indicating a higher sensitivity in the latter. When applied to detect 35 patient with BSIs of AB, the results were consistent with clinical blood culture identification and drug sensitivity tests. Conclusion The dual ddPCR detection method for OXA-23 and gltA developed in this study exhibits good specificity, excellent linearity, and a higher LOD than qPCR. It demonstrates reproducibility even for minute samples, making it suitable for rapid diagnosis and precision treatment of CRAB in BSIs.